2010
DOI: 10.1103/physrevlett.105.167401
|View full text |Cite
|
Sign up to set email alerts
|

Observation of the Intraexciton Autler-Townes Effect inGaAs/AlGaAsSemiconductor Quantum Wells

Abstract: The near-infrared transmission of a semiconductor multiple quantum well is probed under intense terahertz illumination. We observe clear evidence of the intraexcitonic Autler-Townes effect when the terahertz beam is tuned near the 1s-2p transition of the heavy-hole exciton. The strongly coupled effective two-level system has been driven with terahertz field strengths of up to 10  kV/cm resulting in a Rabi energy of ≈0.6 times the transition energy. The induced near-infrared spectral changes at low intensities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
99
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(101 citation statements)
references
References 29 publications
2
99
0
Order By: Relevance
“…However, few studies have been reported on the nonlinear terahertz characteristics of semiconductors using high fields [112,15,113].…”
Section: Nonlinear Thz Spectroscopy Of Semiconductorsmentioning
confidence: 99%
“…However, few studies have been reported on the nonlinear terahertz characteristics of semiconductors using high fields [112,15,113].…”
Section: Nonlinear Thz Spectroscopy Of Semiconductorsmentioning
confidence: 99%
“…The advent of sources of intense terahertz electromagnetic radiation enables the study of semiconductors in a regime where time-dependent perturbation theory fails completely. Exciting new quantum coherent phenomena emerge, including the dynamical Franz-Keldysh effect [6,7], non-linear excitonic effects [8][9][10][11], and highorder sideband generation [12][13][14]. High-order sideband generation is a cousin of high-order harmonic generation from atoms in intense laser fields [15][16][17].…”
mentioning
confidence: 99%
“…As to optical transitions between the dressed states (13) and (14), they can be described by the matrix dipole elementsd where d…”
Section: Model Of Electronic Structurementioning
confidence: 99%
“…Therefore, the system "electron + strong field" is conventionally considered as a composite electron-field object which was called "electron dressed by field" (dressed electron) [1,2]. The field-induced modification of physical properties of dressed electrons was studied in both atomic systems [1][2][3] and various condensed-matter structures, including bulk semiconductors [4][5][6], graphene [7][8][9][10][11], quantum wells [12][13][14][15][16][17], quantum rings [18][19][20][21], quantum dots [22][23][24][25][26][27][28][29][30][31][32], etc. Among these structures, quantum dots (QDs) -semiconductor 3D structures of nanometer scale, which are referred to as "artificial atoms" -seem to be most interesting for optical studies since they are basic elements of modern nanophotonics [33,34].…”
Section: Introductionmentioning
confidence: 99%